Financial Exclusion in Australia: Can Islamic Finance Minimise the Problem? - Mohamed Rosli Mohamed Sain; Mohammad Mafizur Rahman; Rasheda Khanam (Australasian Accounting, Business and Finance Journal, 2016)
The purpose of this study is to explore the nature and extent of financial exclusion in Australia focussing particularly the Muslim community. Financial exclusion refers to a situation where people lack access to affordable and appropriate financial services and products. In 2013, 16.9% of adults living in Australia were severely or fully financially excluded; that is, almost one in six adults had no access to at least two basic financial products. This paper is based on literature reviews, secondary data and the authors’ personal experience in association with banking industry. The finding of this paper concludes that financial exclusion remains a problem in Australia and there is still lack of information about financial exclusion based on ethnicity or religious group in Australia. It also appears that very limited financial institutions in Australia are offering Islamic financial products and services to cater for the needs of some 476,000 Muslims in Australia. These Muslims communities may have been financially excluded due to their faith and religious belief, because Islam prohibits Riba (usury and/or interest) which is widely practiced in conventional banking. Islamic finance can mitigate the severity of the problem.
Keywords: Financial exclusion; Muslims; Australia